2022
DOI: 10.3390/ma15124103
|View full text |Cite
|
Sign up to set email alerts
|

Life-Cycle Assessment of Apartment Buildings Based on Standard Quantities of Building Materials Using Probabilistic Analysis Technique

Abstract: Given the increasingly serious nature of environmental problems, many countries have recently declared carbon neutrality policies and expended efforts to implement them. The domestic building industry aims to reduce its environmental impact using life-cycle assessments (LCAs) of buildings according to the Green Standard for Energy and Environmental Design. However, it is difficult to perform efficient LCAs because the required quantity takeoff process is complex, and the quantity takeoff sheet may not exist du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Moreover, the analysis of the concrete modified with car glass has shown that this additive has little effect on the improvement of the environmental performance of this material. In assessing the impact of concrete on the natural environment, the cement production process plays a significant role, as it is highly material-and energy-consuming, as a result of which a large amount of emissions is generated [91].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the analysis of the concrete modified with car glass has shown that this additive has little effect on the improvement of the environmental performance of this material. In assessing the impact of concrete on the natural environment, the cement production process plays a significant role, as it is highly material-and energy-consuming, as a result of which a large amount of emissions is generated [91].…”
Section: Discussionmentioning
confidence: 99%